Translational Models of Arrhythmia Mechanisms and Susceptibility: Success and Challenges of Modeling Human Disease - Piktel, Joseph S.; Wilson, Lance D. (Frontiers in Cardiovascular Medicine, 2019)
We discuss large animal translational models of arrhythmia susceptibility and sudden cardiac death, focusing on important considerations when interpreting the data derived before applying them to human trials. The utility of large animal models of arrhythmias and the pros and cons of specific translational large animals used will be discussed, including the necessary tradeoffs between models designed to derive mechanisms vs. those to test therapies. Recent technical advancements which can be applied to large animal models of arrhythmias to better elucidate mechanistic insights will be introduced. Finally, some specific examples of past successes and challenges in translating the results of large animal models of arrhythmias to clinical trials and practice will be examined, and common themes regarding the success and failure of translating studies to therapy in man will be discussed.